The Conceptualizations of Authority, Sovereignty, and the State in the Political Thought of Jean-Jacques Rousseau - Belkacem BENCHAIB (Social Sciences Journal, 1970)
The political thought of Jean-Jacques Rousseau is manifested in concepts rooted in the disparities among individuals and groups arising from the relationships inherent in various ideologies and political systems. These differences are shaped by the nature and origin of the state, which often comes at the expense of political systems characterized by a singular political authority. Rousseau's ideas are exemplified in the social contract that underpins the state, founded on popular and democratic principles. The foundational premise of the political hierarchy is the people, who constitute the bedrock of authority and its continuity as a sovereign state, supported by state apparatuses operated by the populace in accordance with this contract. This agreement signifies a total or partial delegation of power from the ruler to the governed, representing them within a unified political framework. This indicates the existence of legislative, executive, and judicial powers, whose roles within the political authority are evident. The political thought illustrated by Rousseau delineates a structure of the state based on the interactive relationships between the executive and legislative powers, which are realized only through popular sovereignty and an organized political authority that stands independently. This reflects a dynamic interaction within the body of authority grounded in civil society and laws adhering to democratic processes, despite differing ideological forms. Ultimately, this serves as a political foundation for the spirit of Rousseau’s political authority, which is based on sovereignty